Концептуальні підходи до оцінки ефективності розвитку підприємства - Швед, Тетяна Володимирівна (My University, 2014)
В статті досліджуються теоретичні та методичні аспекти ефективності розвитку підприємства. Автор досліджує поняття «ефективність», розглядає наявні концептуальні підходи до оцінки ефективності виробництва, ефективності діяльності та ефективності бізнесу, визначає категорію «ефективність розвитку підприємства». Ефективність розвитку підприємства, на переконання автора, характеризується системою показників, які знаходяться в межах факторів внутрішнього і зовнішнього середовища. The article describes the theoretical and methodological aspects of the efficiency the development of an enterprise. The author explores the concept of «efficiency», examines existing conceptual approaches to estimation of efficiency of production, efficiency of activity and business efficiency and determines a category «efficiency the development of an enterprise». Analysis of scientific and applied researches as home, such foreign scientists, gave an opportunity complex and consistently to investigate a concept «development of an enterprise», distinguishing the characteristic signs of this process, that became the initial condition of forming of the own understanding of category «efficiency the development of an enterprise».
Keywords: показники ефективності розвитку підприємства; розвиток підприємства; ефективність діяльності підприємства; ефективність виробництва; ефективність бізнесу; ефективність розвитку підприємства; indexes of efficiency the development of an enterprise; development of an enterprise; effectiveness of enterprises; production efficiency; business efficiency; кафедра економічної теорії